Assessment of Number of Layers on Tensile and Bend Strength of HB 500 and ST 42 Dissimilar Weldments - Cut Fitria; Arif Tjahjono; Iwan Setiawan (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2021)
The joining of several materials with different characteristics has been widely carriedout for industrial progress, especially to obtain material characteristics that are superior to theprevious one. One of the most common joining techniques is welding. This research wasconducted to determine the weldability of different steels with the number of layers varyingbetween 3 and 4 layers. The object of this research is the welded connection of HB 500 wear-resistant steel plate with ST 42 construction steel plate where the thickness of each material is 10mm. Welding with the Gas Metal Arc Welding (GMAW) method employes ER 70 S filler metal ineach layer and currents from 90 A to 180 A at each connection. Tensile and bending tests werecarried out as a characterization of the weld area to determine its mechanical properties. Theresults show a significant effect of the number of layers on the quality of the connection. Theoptimum value is formed in the number of infill layers as much as 4 layers with tensile strengthof 448.37 - 473.292 MPa, yield stress of 305.767 - 317.493 MPa, elongation of 33.8 - 34.56%, andable to bend under load 874,498 - 919,544 MPa with angle formed are 85.414° on the root and86.14° on the face.